2021
DOI: 10.1111/cns.13691
|View full text |Cite
|
Sign up to set email alerts
|

Altered mismatch response of inferior parietal lobule in amnestic mild cognitive impairment: A magnetoencephalographic study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
(178 reference statements)
0
6
0
Order By: Relevance
“…In the brain node attention module, we set up multiple base layers to capture the brain regions related to MCI. The experiments in this article found that 34 brain regions in all brain regions are closely related to MCI, including the middle temporal gyrus controls semantic cognition (Davey et al, 2016 ); the Superior frontal gyrus medial orbitally affects schizophrenia and delusions (Gao et al, 2015 ); Inferior parietal affects sensory memory function Chen et al ( 2021 ); Supramarginal gyrus affects auditory memory function (DES, 2014 ); and Precuneus affects cognitive function (Nagano-Saito et al, 2021 ). These brain nodes are correlated with MCI and are consistent with the experimental results of previous studies (Greicius, 2008 ; Albert et al, 2011 ).…”
Section: Discussionmentioning
confidence: 93%
“…In the brain node attention module, we set up multiple base layers to capture the brain regions related to MCI. The experiments in this article found that 34 brain regions in all brain regions are closely related to MCI, including the middle temporal gyrus controls semantic cognition (Davey et al, 2016 ); the Superior frontal gyrus medial orbitally affects schizophrenia and delusions (Gao et al, 2015 ); Inferior parietal affects sensory memory function Chen et al ( 2021 ); Supramarginal gyrus affects auditory memory function (DES, 2014 ); and Precuneus affects cognitive function (Nagano-Saito et al, 2021 ). These brain nodes are correlated with MCI and are consistent with the experimental results of previous studies (Greicius, 2008 ; Albert et al, 2011 ).…”
Section: Discussionmentioning
confidence: 93%
“…The IPL, including the ANG, is regarded as a hub for information transmission and integration 99 . Numerous investigations have revealed that IPL is associated with a wide variety of cognitive impairments 100 102 . Meanwhile, several studies have found altered FC of the IPL in migraineurs than in healthy controls 103 105 .…”
Section: Discussionmentioning
confidence: 99%
“…The IPL supports an extensive range of cognitive functions, including visuospatial attention, memory, motor planning, and mathematical cognition (Uddin et al, 2010 ). The left IPL, vital for the storage of visual short‐term memory (Chen et al, 2021 ; Henson et al, 2000 ; Todd & Marois, 2004 ), is considered a promising biomarker to distinguish aMCI from HC (Hänggi et al, 2011 ). Particularly, the peak MNI coordinate of IPL in our study was located in the angular gyrus.…”
Section: Discussionmentioning
confidence: 99%